Current status of liver transplantation. - Friend, P; Imber, C (2006)
Liver transplantation has become the treatment of choice for a wide range of end-stage liver disease. As outcomes have improved, so the demand for this therapy has increasingly exceeded the availability of donor organs. Access to liver transplantation is controlled such that donor organs are generally allocated to the patients who are likely to benefit most, although if all patients who might benefit were placed on the waiting list, the donor shortage would be greatly increased. Recurrence of the original liver disease is emerging as an important issue. Fewer patients are transplanted for liver tumors, as earlier results showed a very high rate of recurrence. In recent years there has been a change in the underlying conditions of patients on the waiting list, and a preponderance of patients now present with hepatitis C and alcoholic cirrhosis. Increasingly, transplant units are looking to sources of donor organs that would previously have been deemed unsuitable--such marginal donors include non-heart-beating donors (NHBDs). Results from controlled NHBDs--those cases in which cardiac arrest is predicted--suggest that this is a good source of viable organs. Splitting a donor liver to provide two grafts has successfully enabled the transplantation of a child and an adult from one organ. The transplantation of two adults from a single organ remains a greater challenge. Transplantation from living donors has been practiced increasingly over the last decade, although anxieties have been expressed over donor safety. In many countries this now represents a significant contribution to overall liver transplant activity.